Pathogen-responsive gene cluster for highly modified fatty acids in tomato - Jeon, Ju Eun (Cell, 2020)
In response to biotic stress, plants produce suites of highly modified fatty acids that bear unusual chemical functionality. Despite their chemical complexity and proposed roles in pathogen defense, little is known about the biosynthesis of decorated fatty acids in plants. Falcarindiol is a prototypical acetylenic lipid present in carrot, tomato, and celery that inhibits growth of fungi and human cancer cell lines. Using a combination of untargeted metabolomics and RNA sequencing, we discovered a biosynthetic gene cluster in tomato (Solanum lycopersicum) required for falcarindiol production. By reconstituting initial biosynthetic steps in a heterologous host and generating transgenic pathway mutants in tomato, we demonstrate a direct role for the cluster in falcarindiol biosynthesis and resistance to fungal and bacterial pathogens in tomato leaves. This work reveals a mechanism by which plants sculpt their lipid pool in response to pathogens and provides critical insight into the complex biochemistry of alkynyl lipid production.